1-[2-(1,3-benzothiazol-2-ylimino)imidazolidin-1-yl]ethanone - Yildirim, SÖ; Akkurt, M; Servi, S; Sekerci, M; Fun, HK (Int Union Crystallography, 2006)
With the exception of seven H atoms, the molecule of the title compound, C12H12N4OS, is planar. Two intramolecular N-H center dot center dot center dot N and C-H center dot center dot center dot N hydrogen bonds are observed in the crystal structure.
Keywords: 2-Arylamino-2-Imidazolines; Derivatives